The Utility of Sodium Channel Provocation in Unexplained Cardiac Arrest Survivors and Electrocardiographic Predictors of Ventricular Fibrillation Recurrence. (28th November 2022) - Ensam, Bode; Cheung, Christopher C.; Almehmadi, Fahad; Gregers Winkel, Bo; Scrocco, Chiara; Brennan, Paul; Leong, Kevin; Muir, Alison; Vanarva, Amanda; Tfelt-Hansen, Jacob; Roberts, Jason D.; Krahn, Andrew D.; et al.
Abstract : Background: The implications of a drug-induced type 1 Brugada ECG pattern following sodium channel blocker provocation (SCBP) are not fully understood. Methods: Baseline clinical and ECG data were obtained from consecutive unexplained cardiac arrest survivors undergoing SCBP at 3 centers. A further 15 SCBP positive (SCBP+) unexplained cardiac arrest survivors were recruited from 3 additional centers to explore ventricular fibrillation recurrence. Results: A total of 121 consecutive unexplained cardiac arrest survivors underwent SCBP. The yield of the drug-induced type 1 Brugada ECG pattern was 17%. A baseline type 2/3 Brugada pattern (T2/3BP) (adjusted odds ratio, 19.36 [2.74–136.61]; P =0.003) and PR interval (odds ratio, 1.03 [1.01–1.05] per ms; P =0.017) were independent predictors of SCBP+ response. A pathogenic SCN5A variant was identified in 36% of the SCBP+ group versus 0% in the SCBP− group ( P <0.001). Amongst SCBP+ patients, a spontaneous type 1 Brugada pattern was identified in 19% during follow up and in 24% a type 1 Brugada pattern was identified in a relative. Prior syncope (adjusted hazard ratio, 3.83 [1.36–10.78]; P =0.011) and the presence of global early repolarization (hazard ratio, 7.91 [3.22–19.44]; P <0.001) were independent predictors of 5-year ventricular fibrillation recurrence. There was a nonsignificant trend toward greater 5-year ventricular fibrillation recurrence in the SCBP− group (23/95 [24%] versus 3/34 [9%]; P =0.055). Conclusions: The yield of the drug-induced type 1 Brugada ECG pattern in consecutive unexplained cardiac arrest survivors undergoing SCBP is 17%. A baseline T2/3BP and PR interval were independent predictors of the drug-induced type 1 Brugada ECG pattern. Greater heritability of BrS phenotype in this group was evidenced by a greater prevalence of pathogenic SCN5A variants and relatives with a type 1 Brugada pattern. A history of prior syncope and the presence of global early repolarization were independent predictors of ventricular fibrillation recurrence.